Do Consumers Choose the Right Credit Contracts? - Agarwal, Sumit; Chomsisengphet, Souphala; Liu, Chunlin; Souleles, Nicholas S. (The Review of Corporate Finance Studies, 2015)
We analyze an experiment conducted by a large U.S. bank that offered consumers achoice between two credit card contracts, one with an annual fee but a lowerinterest rate and one with no annual fee but a higher interest rate. We findthat on average consumers chose the credit contract that minimized their costs.A substantial fraction of consumers (about 40%) still chose the suboptimalcontract. Nonetheless, the probability of choosing the suboptimal contractdeclines with the dollar magnitude of the potential error, and consumers withlarger errors are more likely to subsequently switch to the optimalcontract.